Least-squares estimation for a long-horizon performance index - Janiszowski, Krzysztof B. (Zielona Góra: Uniwersytet Zielonogórski)
Estimation of a parametric, discrete-time model for a SISO dynamic plant, derived for minimisation of a performance index determined as a sum of squared prediction errors within some time horizon is considered. A formula for a Long-Horizon Least-Squares (LHLS) off-line solution as well as a theorem for an LHLS recursive on-line scheme are derived.
Keywords: identification; least-squares estimation; prediction; recursive scheme